2005
DOI: 10.1002/cncr.21490
|View full text |Cite
|
Sign up to set email alerts
|

Survivin expression and its relation with proliferation, apoptosis, and angiogenesis in brain gliomas

Abstract: BACKGROUND An unbalance of cell proliferation and cell apoptosis is an important mechanism in carcinogenesis, and angiogenesis also plays a crucial role in tumorigenesis. Recently, survivin has been identified as an important member of the inhibitor of apoptosis protein (IAP) family. Although it has been shown that survivin is highly expressed in gliomas, and is associated with tumorigenesis, progression, and poor prognosis of gliomas, as yet the relation of survivin expression with proliferation, apoptosis, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 49 publications
3
66
0
Order By: Relevance
“…Because survivin is overexpressed in a variety of tumors including gliomas, 15 we wanted to explore whether survivin is also overexpressed in the tumor vasculature. To accomplish this, we immunostained cell preparations of TuBECs and BECs with an antibody to survivin.…”
Section: Tubecs Express High Levels Of Survivin In Vitro and In Situ mentioning
confidence: 99%
See 1 more Smart Citation
“…Because survivin is overexpressed in a variety of tumors including gliomas, 15 we wanted to explore whether survivin is also overexpressed in the tumor vasculature. To accomplish this, we immunostained cell preparations of TuBECs and BECs with an antibody to survivin.…”
Section: Tubecs Express High Levels Of Survivin In Vitro and In Situ mentioning
confidence: 99%
“…13 In various tumors, high survivin levels are correlated with poor prognosis, decreased apoptosis, increased angiogenesis, and chemoresistance in cancer cell lines. 14,15 However, little is known of survivin's function in the endothelial cells of the tumor vasculature.…”
mentioning
confidence: 99%
“…2 It is widely expressed in a strictly regulated manner during embryonic development but rarely detected in normal tissues. 3 By contrast, survivin is prominently overexpressed in most malignant tumors, especially in colon cancer, such as SW480, HCT116 and CT26 and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the elevated survivin expression is associated with increased microvessel density in colorectal cancer (9), colon cancer (23) and brain glioma (33). Increased survivin expression has been verified in endothelial cells during the proliferative (25,34,35) and remodeling (36,37) phases of angiogenesis, potentially serving as a cytoprotective mechanism for these cells (35).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, induction of survivin in endothelial cells is associated with resistance to apoptosis. In contrast, survivin is undetectable in quiescent endothelium in vitro and in vivo (25), and targeting survivin does not affect endothelial cell viability in quiescent endothelium (33). Thus, inhibition of survivin may promote endothelial cell apoptosis during tumor angiogenesis, accelerating regression of newly formed blood vessels and reducing the incidence of metastatic disease.…”
Section: Discussionmentioning
confidence: 99%